Increasing the sensitivity of surface-enhanced Raman scattering detection for s-triazine pesticides by taking advantage of interactions with soil humic substances - Rubira, Rafael J. G. [UNESP]; Camacho, Sabrina A. [UNESP]; Constantino, Carlos J. L. [UNESP]; Sanchez-Cortes, Santiago (Wiley, 2022)
Surface-enhanced Raman scattering (SERS) is a technique which has been well explored for detecting contaminating substances, such as pesticides. Of particular interest has been the use of SERS for quantifying trace levels of the s-triazine compounds, unraveling the adsorption mechanisms on metallic nanoparticles. Herein, we applied silver nanoparticles (AgNP) as SERS substrates for detecting commercial samples of the pesticides prometryn (PRM) and atrazine (ATZ) and their purified samples in the presence of soil humic substances (SHS). The degrading effect of SHS was assessed through the similarities between the SERS spectra of the purchased pesticides and purified pesticides in the presence of SHS. We also evaluated the mechanisms of interaction between the purified pesticide molecules and SHS. Strong interactions of the amino groups (s-triazine molecules) with the oxygenated groups (SHS) were confirmed via SERS spectra. Such interaction, which is favorable for purified pesticides, allowed to increase the sensitivity of SERS detection, reaching low limits of detection (LOD): 5.5 ppb and 4.0 ppb for unpurified PRM and ATZ (as purchased), respectively, against 1.3 ppb and 21 ppt for purified PRM and ATZ in the presence of the SHS, respectively.